Physical, chemical and organoleptic characteristics of low alcohol beverages basedon sugar sorghum - Karputina, Margarita; Khargeliia (Karputina), Daria; Melnyk, Iryna (My University, 2019)
The paper evaluates the modern market of soft drinks. The production of soft drinks is characterized by an extremely wide variety of raw materials. The use of juices, concentrates, infusions and extracts of plant raw materials, flavors, emulsions, aromatic bases, food acids, vitamins, dyes, stabilizers, preservatives, brighteners, turbidizers, sweeteners and other raw materials and materials that meet the requirements of applicable regulations and have permission Ministry of Health. It is established that the increase in demand for these beverages will be with the use in the technology of natural plant materials, which are biologically active substances. Sugar sorghum is offered as a high-quality raw material, which is a promising crop and is characterized by a rich component composition. It is proposed to obtain weak drinks by fermenting the wort on the basis of sugar sorghum juice with the addition of apple and apple-cherry concentrates. Physico-chemical parameters of the wort are determined and the modes of its fermentation by dry yeast of the manufacturer "Biowin" - Brewgo-01 and the manufacturer "Fermivin" - Gervin GV1 are proposed, which are considered for brewing and wine dilutions, respectively. The influence of these placers on the accumulation of potential food products and the formation of organoleptic characteristics of beverages has been studied. It was found that in the studied samples of the best products are in quantities close to the threshold of sensation and, of course, affect the taste and aroma profile of finished drinks. Profilograms of taste and aroma and the made product about prospects of use of salted sorghum in technologies of low-alcoholic drinks on the basis of natural raw materials are constructed.
Keywords: слабоалкогольні напої; побічні продукти бродіння; сусло; цукрове сорго; сухі дріжджі; low-alcohol beverages; sugar sorghum; wort; dry yeast; fermentation by-products; кафедра біотехнології продуктів бродіння і виноробства